VD_FINDINFO ML / 2013 / 43 vom 14. Januar 2013 - VD Tribunal cantonal (2013)
MAINLEVÉE DÉFINITIVE, OBLIGATION D'ENTRETIEN, APPRENTISSAGEFORMATION PROFESSIONNELLE | 277 al. 2 CC, 289 al. 2 CC, 344a CO, 80 LP